ANALISIS LITERASI EKONOMI - Sina, Peter Garlans (Jurnal Economia, 2012)
Abstract: Analysis of Economic Literacy. The aim of this research is as an effort to increase economic literacy for individuals and households who want to achieve prosperity. Therefore, the obligation of improving the economic literacy needs to be done in a well-planned manner and come from the strong intention to learn in order to improve the economic literacy. It could have an effect on the assets accumulation, a better debt management, as a protection, as well as to increase savings and managing spending intelligently. Keyword: economic literacy, asset, debt, protection, saving, spending Abstrak: Analisis Literasi Ekonomi. Tulisan ini bertujuan sebagai upaya meningkatkan literasi ekonomi bagi individu maupun rumah tangga yang menginginkan mencapai kesejahteraan. Oleh karena itu, kewajiban meningkatkan literasi ekonomi perlu dilakukan secara terencana dan diawali dari niat untuk belajar meningkatkan literasi ekonomi karena dapat berefek pada akumulasi aset, pengelolaan utang yang tepat, proteksi, meningkatkan tabungan dan cerdas mengelola pengeluaran. Kata kunci: literasi ekonomi, aset, utang, proteksi, menabung, pengeluaran